Analisis Pola Penanganan Sampah Rumah Tangga dan Distribusi Infrastruktur Persampahan di Kota Gorontalo - Sri Maryati; Budiyanto Ahaliki; Rahmat Taufik R.L Bau; Hermila A; Adnan Engelen (Universitas Negeri Gorontalo, 2025)
Urban waste is a complex environmental issue, particularly in mid-sized cities like Gorontalo City, where the increase in generation is disproportionate to the capacity of management infrastructure. This study aims to analyze household waste management patterns and evaluate the distribution of waste infrastructure. A descriptive quantitative approach was used through a stratified sampling survey of 400 households in nine sub-districts. The results showed that 46.5% of respondents rely on Government Environmental Agency services, while 15% still burn waste and 6.3% dispose of it in rivers or vacant lots. Thirty-three percent of respondents assessed irregular collection, with service disparities clearly visible between central and outlying sub-districts. An analysis of infrastructure distribution revealed uneven distribution of recycling waste management units, with Kota Selatan sub-district lacking such facilities. Community suggestions emphasized the addition of fleets, segregated recycling waste management units, education, waste banks, and the use of digital technology. This study concluded that successful waste management is determined not only by technical aspects but also by regulations, institutions, education, and community participation.